CONCEPTUAL METAPHORS OF RACE AND ALIENATION IN THE ALBUM NEGRO SWAN BY BLOOD ORANGE - Alya, Naysilla Kharisma; Nita, Febidian (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
This research examines how conceptual metaphors in six songs from Blood Orange’s Negro Swan album represent themes of racial identity and alienation. Using Lakoff and Johnson’s Conceptual Metaphor Theory, the study adopts a qualitative descriptive method to identify and interpret metaphorical expressions found in the lyrics of “Charcoal Baby,” “Orlando,” “Jewelry,” “Dagenham Dream,” “Runnin’,” and “Minetta Creek.” The analysis reveals that metaphors related to race emphasize concepts of otherness, hypervisibility, surveillance, and the social devaluation of Black bodies. Meanwhile, metaphors of alienation are expressed through spatial and emotional imagery, such as downward orientation, confinement, repetitive motion, and identity masking. These metaphors work collectively to frame racialization and marginalization shapes emotional displacement. The findings demonstrate that conceptual metaphors in Negro Swan do not function merely as stylistic devices but as cognitive tools that structure how experiences of Blackness and vulnerability are understood. By combining cognitive metaphor theory with the study of contemporary music, this research fills a gap in existing scholarship on racialized experience and alienation in lyrical expression.